Cost-effective analysis of unilateral cochlear implantation under the Taiwan national healthcare insurance. (2nd January 2020) - Fang, Te-Yung; Cheng, Li-Jen; Wu, David Bin-Chia; Wang, Pa-Chun
Abstract: Objective: The value of cochlear implantation (CI) has not been established in Taiwan. The purpose of this study was to evaluate the cost-effectiveness of paediatric CI within the context of Taiwan's national health insurance (NHI) programme. Design: A Markov model-based cost-utility analysis (CUA) was conducted to evaluate the cost-effectiveness of a unilateral CI (UCI) with a contralateral acoustic hearing aid (UCI-HA) compared with a bilateral HA. We performed one-way sensitivity analyses to identify the cost variables that affected the incremental cost-effectiveness ratio (ICER) the most. Monte Carlo simulation was used to explore the simultaneous effect of all uncertain parameters on cost-effectiveness. Study sample: Not applicable. Results: Compared with bilateral HAs, the ICER for UCI-HA was $6487 per quality-adjusted life year (QALY) gained. The ICERs were consistently below $7000 per QALY gained and were most sensitive to the selling price of the external CI device. When this selling price increased by 10%, the ICER of UCI-HA would increase to $6954 per QALY gained. UCI-HA has a probability greater than 50% of being cost-effective if the cost-effectiveness threshold exceeds approximately $10, 000 per QALY. Conclusions: Our analysis suggested that within the context of Taiwan's NHI programme, UCI is highly cost-effective for deaf children.